What can eye movements tell about students’ interpretations of contextual graphs? A methodological study on the use of the eye-mind hypothesis in the domain of functions - Thomaneck, Aylin; Vollstedt, Maike; Schindler, Maike (Frontiers in Education, 2022)
Introduction The use of eye tracking (ET) in mathematics education research has increased in recent years. Eye tracking is a promising research tool in the domain of functions, especially in graph interpretation. It promises to gain insights into learners’ approaches and ways of thinking. However, for the domain of functions and graph interpretation, it has not yet been investigated how eye-tracking data can be interpreted. In particular, it is not clear how eye movements may reflect students’ cognitive processes. Thus, in this study, we investigate in how far the eye-mind hypothesis (EMH), which states broadly that what the eye fixates is currently being processed, can be applied to this subdomain. This is particularly true for contextual graphs, whose data originate from real-world situations, and which are of central importance for the development of mathematical literacy. The aim of our research is to investigate how eye movements can be interpreted in the domain of functions, particularly in students’ interpretations of contextual graphs. Methods We conducted an exploratory case study with two university students: The students’ eye movements were recorded while they worked on graph interpretation tasks in three situational contexts at different question levels. Additionally, we conducted subsequent stimulated recall interviews (SRIs), in which the students recalled and reported their original thoughts while interpreting the graphs. Results We found that the students’ eye movements were often related to students’ cognitive processes, even if indirectly at times, and there was only limited ambiguity in the interpretation of eye movements. However, we also found domain-specific as well as domain-general challenges in interpreting eye movements. Discussion Our results suggest that ET has a high potential to gain insights into students’ graph interpretation processes. Furthermore, they point out what aspects, such as ambiguity and peripheral vision, need to be taken into consideration when investigating eye movements in the domain of functions.